Impact of Patient Age on the Frequency of Urethrocutaneous Fistula After Hypospadias Repair Using Autologous Platelet-Rich Fibrin - Ghazi, Waqar Hameed (Indus Journal of Bioscience Research, 2025)
Background: Urethrocutaneous fistula (UCF) remains the most common complication after hypospadias repair. Autologous platelet-rich fibrin (PRF) has emerged as a biological sealant to improve surgical outcomes. However, the impact of patient age on UCF formation despite PRF use remains under-explored. Objective: To determine the frequency of urethrocutaneous fistula in children aged 1–6 years versus 7–12 years undergoing hypospadias repair with PRF as an intermediate layer. Methods: This was a prospective observational study conducted over 12 months at the Department of Pediatric Surgery, Services Hospital, Lahore. A total of 139 male patients undergoing primary hypospadias repair were included. Patients were divided into two groups based on age: Group A (1–6 years, n=87) and Group B (7–12 years, n=52). All surgeries utilized the tubularized incised plate (TIP) urethroplasty technique with PRF application between the neourethra and skin. Patients were followed for 3 months postoperatively for development of UCF. Data were analyzed using SPSS 25.0, and chi-square test was applied to determine statistical significance (p<0.05). Results: The overall frequency of UCF was 7.9% (11/139). In Group A, 4 out of 87 patients (4.6%) developed UCF, while in Group B, 7 out of 52 patients (13.5%) developed UCF. The difference was statistically significant (p<0.05), indicating higher complication rates in older children. Conclusion: Hypospadias repair in children aged 1–6 years is associated with significantly lower rates of urethrocutaneous fistula even when PRF is used. Early surgical intervention is recommended to minimize postoperative complications and optimize the benefits of PRF application.